Teaching Islamic studies in the age of ISIS, Islamophobia and the Internet - Dorroll, Courtney M. (Encounters: Explorations in Folklore and Ethnomusicology Ser., 2019)
How can teachers introduce Islam to students when daily media headlines can prejudice students' perception of the subject? What are strategies for discussing Islam and violence without perpetuating stereotypes? Teaching Islamic Studies in the Age of ISIS, Islamophobia, and the Internet provides clear, feasible suggestions and theoretical tools to address the challenges teachers of Islamic Studies face